Facial aging and orofacial harmonization – a narrative literature review (Research, Society and Development, 2023)
Observing the increase in the elderly population, as well as the growing appreciation of appearance, the dental specialty of orofacial harmonization makes it possible to improve the quality of life through facial treatments. However, knowledge of the processes associated with aging is necessary to indicate individualized treatment. Skin aging, whether intrinsic or extrinsic, is directly associated with aesthetics that are considered inadequate and require interventions to correct them. Therefore, this research seeks, through a narrative review of the literature, to offer dentists a document that catalogs the status quo of the facial aging process and the need to understand it for the correct planning of treatment associated with harmonization. Data collection took place in the PubMed, LILACS and Scielo databases, indicating the following descriptors in the search field: “Face”, “Aging” and “Cellular Senescence”. There was no restriction on the type of literature to be included in the references. In conclusion, the facial aging process is a complex and multifaceted phenomenon, influenced by several theories of facial aging. It is important for specialists in orofacial harmonization to have a broad knowledge of this process, as well as theories of aging, in order to be able to offer individualized and effective treatments that improve the quality of life of patients. By understanding the structural and aesthetic changes that occur during facial aging, professionals can apply harmonizing practices that aim to improve facial symmetry, restore lost volume and smooth wrinkles and expression lines, helping patients to regain self-confidence and self esteem.